2018
DOI: 10.2147/cia.s164108
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the acute effects of traditional versus high velocity resistance training on metabolic, cardiovascular, and psychophysiological responses in elderly hypertensive women

Abstract: ObjectivesThe aim of the present study was to compare the acute effects of traditional resistance training (RT) versus high velocity RT (HVRT) on metabolic, cardiovascular, and psychophysiological responses in elderly hypertensive women.MethodsFifteen elderly women (mean age ± standard deviation, 67.1±6.9 years) classified as having hypertension stage 1 or 2 were randomly allocated to complete traditional RT or HVRT; 1 week later, subjects allocated to RT completed the HVRT session and vice-versa. Heart rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
11
1
1
Order By: Relevance
“…Although discrepancies exist among the investigations, the present results and others [11,25] suggest that a power exercise or HVRE session elicits PEH in hypertensive older adults. Different from previous studies that have assessed BP post-exercise during a very short-term period in a laboratory setting [10,11,25], the present study showed in a sample of hypertensive older women that a HVRE session elicited a systolic PEH up to 4 h post-exercise in free-living conditions. This BP reduction observed in the present investigation may have attenuated the overload imposed to the subjects' cardiovascular system during their daily activities, which is clinically meaningful.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Although discrepancies exist among the investigations, the present results and others [11,25] suggest that a power exercise or HVRE session elicits PEH in hypertensive older adults. Different from previous studies that have assessed BP post-exercise during a very short-term period in a laboratory setting [10,11,25], the present study showed in a sample of hypertensive older women that a HVRE session elicited a systolic PEH up to 4 h post-exercise in free-living conditions. This BP reduction observed in the present investigation may have attenuated the overload imposed to the subjects' cardiovascular system during their daily activities, which is clinically meaningful.…”
Section: Discussioncontrasting
confidence: 92%
“…Machado et al [25] reported a systematic occurrence of PEH following power exercise sessions performed over a 12-week period of a power training intervention in older women with type 2 diabetes. On the contrary, no PEH following a single power-exercise session was observed by Orsano et al [10], who compared traditional resistance exercises and power exercises using weight-training equipment up to 45 min post-exercise. No changes were observed for BP, despite a lower HR and an increased NO bioavailability 30 min post-exercise.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Evidence indicates that elevated body fat and hypertension are responsible for increased oxidative stress in elderly persons. 36,37 So far, it should be noted that, there have not been reports documenting healthy elderly persons only with insulin-resistance and higher damage oxidative marker (TBARS) which correlates negatively with age. Moreover, it is particularly interesting that our investigated elderly population had higher TBARS in insulin-sensitive ones.…”
Section: Discussionmentioning
confidence: 99%
“…Os achados dessa revisão indicaram ainda que quatro estudos (FELIPE et al, 2018;ORSANO et al, 2018;PAGONAS et al, 2017;BERTANI et al, 2016) não atribuíram benefícios à prática de exercícios resistidos sobre a PA de pessoas com hipertensão.…”
Section: Discussionunclassified